Primary Tracheal Schwannoma With Extension to the Thyroid Gland: Management - Srijana Thapa; Ranjan Sapkota; Srijana Khati; Aayush Adhikari (Clinical Case Reports)
ABSTRACT The occurrence of neurogenic tumors in the tracheobronchial tree is uncommon. We report a case of transmural tracheal schwannoma with extraluminal component extending upto the left thyroid lobe. 40‐year‐old male presented with scanty hemoptysis due to transmural tracheal schwannoma with extraluminal part of tumor extending till the left lobe of thyroid gland. Patient underwent tracheal resection and anastomosis with en‐bloc excision of left thyroid lobe due to the nature and size of the tumor. Tracheal Schwannoma are not that frequent. Symptoms can misguide the clinician causing delay in diagnosis from the onset of symptoms. Definitive diagnosis is made after histopathological examination and immunohistochemical studies. So far, resection and anastomosis of trachea has been adequate treatment. Tracheal neoplasms are unusual and tracheal schwannomas are very unique. The case highlights the varied presentation of tracheal schwannoma and confusion faced to diagnose the patient and provide an optimal management.